OS NOVOS TEMPOS: O olhar satírico de Leandro Gomes de Barros - PINTO, Bruna Costa (2024)
The beginning of the First Republic in Brazil was marked by many changes due to the transition from a monarchical to a republican government. The country adopted a presidential system, pursued industrialization more aggressively, and embraced ideals of modernization, particularly with the advent of the Belle Époque. Additionally, this period saw the end of the patronage system, meaning the separation between Church and State. The popular poet Leandro Gomes de Barros (1865–1919), keenly observant of the societal changes, conveyed these "novelties" to his audience through his satirical lens, often expressing disapproval of the new times. For this research, we have selected the following cordéis for analysis: A secca do Ceará [19-], A Alma de um fiscal [19-], Pannellas que muitos mexem [19-], O fiscal e a lagarta [19-], O governo e a Lagarta contra o fumo [19-], O imposto e a fome [1909], O povo na cruz [19-], Padre Nosso do Impôsto [19-]. In these pamphlets, the poet expresses dissatisfaction with the increase in taxes, the arbitrary actions of the government and its representatives, such as tax collectors, and the disparities between different regions of the country.In the cordéis As cousas mudadas [19-], As Saias calções [1911?], and O Bataclan moderno [19-], the author critique the changes related to women, their clothing, and behavior. O diabo confessando um nova seita [The Devil Confessing a New Sect] [19-] satirizes Protestants, while Affonso Penna [1906], and Os collectores da Great Western [The Great Western Collectors] [19-] critique the expansion of English imperialism. The general objective of this study was to analyze the satire of the republican government in Leandro Gomes de Barros's work. The specific objectives were: to understand the historical context of the pamphlets' production; to grasp the motivations behind the poet's criticisms of the republican government and other contemporary figures; to examine how these critical perspectives are conveyed through poetic construction; and to analyze the aesthetic resources of satire present in the selected pamphlets. To achieve this, the study is divided into three chapters: the first chapter outlines conceptualizations of satire and its various forms; the second chapter analyzes satire directed at the republican government; and the third chapter briefly covers critiques of fashion, female emancipation, English imperialism, and Protestantism. At the end of this dissertation, we come to the conclusion that Gomes de Barros employed satire to critique the measures, injustices, and favoritism exhibited by the Republican government and its representatives, as well as to express his aversion to modernity as it relates to public power and other social elements.